Cases of electronic evidence in Malaysian courts: the civil and syariah perspective - Mohamed, Duryana; Ramlee, Zulfakar (2013)
Islamic law emphasises on justice and fairness in solving disputes. In order to achieve this objective the legal fraternity has developed a procedural law to successfully executing the fairness. Since Islamic law is comprehensive and applicable at any time, the fairness is to be exercised regardless of new development in law and technology. In Islamic law, evidences in electronic formats or cyber evidences are acceptable in certain cases if they are authentic and reliable. Although these evidences carry different name from conventional evidence but their characteristics are similar. They are also very fragile and could easily be altered. Therefore the issues of authenticities are paramount for electronic evidences. This paper will discuss cases that accept electronic evidences in both Islamic and Malaysian law. The discussion will also include the procedure to accept electronic evidence in Malaysian courts and few challenges in establishing the admissibility of electronic evidence.